Evaluation of alginate as a substitute for root‐surrounding tissues in electronic root canal measurements. (3rd July 2012) - Lipski, Mariusz; Trąbska‐Świstelnicka, Marlena; Woźniak, Krzysztof; Dembowska, Elżbieta; Droździk, Agnieszka
Abstract Alginate as a substitute for root‐surrounding tissue was investigated. The electronic working lengths of root canals under clinical conditions were compared with an in vitro simulation of the same teeth extracted and embedded in alginate. The working lengths in 26 teeth were determined on two occasions using an electronic apex locator, before extraction and after extraction with the same teeth embedded in an alginate mass. The apical 4 mm of the root canals were exposed following the measurements, and the distances between the apical constrictions and the tips of files repositioned in the canals were measured and recorded. The mean distance between the file tip and the constriction was +0.33 mm (±0.38) in vivo and +0.32 mm (±0.30) in vitro. The Wilcoxon signed‐rank test indicated that these means were not significantly different. The apical constriction was assessed to be within the limits of 0.5 mm in 80.7% of in vivo cases and in 76.9% of extracted teeth. Statistical analysis demonstrated that there was no significant difference between the results recorded in vivo and in vitro regarding apical constriction localisation. Based on the results of this study, the alginate mass is a useful tool in evaluating the performance of electronic apex locators.